Vernalization Mediated Changes in the Lolium perenne Transcriptome - Paina, Cristiana (Public Library of Science, 2014)
Vernalization is a key requirement for the induction of flowering in perennial ryegrass (Lolium perenne L.). The transcriptome of two genotypes with contrasting vernalization requirement was studied during primary (vernalization and short day conditions) and secondary induction (higher temperature and long day conditions) using an RNA-Seq approach. This revealed transcripts with expression profiles indicative of a role in floral induction, both in the promotion and repression of flowering. We observed similarities and specific differences between the two genotypes related to cold response, carbohydrate metabolism, and photoperiod regulation. Components of the photoperiod pathway showed regulation during vernalization, pointing to possible interactions between elements of the photoperiod and vernalization pathways. The results provide a global picture of the processes ongoing during the transition from vegetative to reproductive phase of perennial ryegrass genotypes with and without a vernalization requirement.